Characterization of Loss-Of-Function KCNJ2 Mutations in Atypical Andersen Tawil Syndrome - Le Tanno, Pauline; Folacci, Mathilde; Revilloud, Jean; Faivre, Laurence; Laurent, Gabriel; Pinson, Lucile; Amedro, Pascal; Millat, Gilles; Janin, Alexandre; Vivaudou, Michel; Roux-Buisson, Nathalie; Fauré, Julien (Frontiers in Genetics, 2021)
Andersen-Tawil Syndrome (ATS) is a rare disease defined by the association of cardiac arrhythmias, periodic paralysis and dysmorphic features, and is caused by KCNJ2 loss-of-function mutations. However, when extracardiac symptoms are atypical or absent, the patient can be diagnosed with Catecholaminergic Polymorphic Ventricular Tachycardia (CPVT), a rare arrhythmia at high risk of sudden death, mostly due to RYR2 mutations. The identification of KCNJ2 variants in CPVT suspicion is very rare but important because beta blockers, the cornerstone of CPVT therapy, could be less efficient. We report here the cases of two patients addressed for CPVT-like phenotypes. Genetic investigations led to the identification of p.Arg82Trp and p.Pro186Gln de novo variants in the KCNJ2 gene. Functional studies showed that both variants forms of Kir2.1 monomers act as dominant negative and drastically reduced the activity of the tetrameric channel. We characterize here a new pathogenic variant (p.Pro186Gln) of KCNJ2 gene and highlight the interest of accurate cardiologic evaluation and of attention to extracardiac signs to distinguish CPVT from atypical ATS, and guide therapeutic decisions. We also confirm that the KCNJ2 gene must be investigated during CPVT molecular analysis.